Screening and activity of potential gastrointestinal probiotic lactic acid bacteria against Yersinia ruckeri O1b - Amin, M; Mark Adams; Burke, CM; Christopher Bolch (2023)
Yersiniosis of cultured Atlantic salmon is a recurrent fish health management challenge in many continents. The causative organism, Yersinia ruckeri , can reside latently in the gut and lead to acute infection and disease during hatchery and sea-transfer stages. One potential prevention approach is the administration of probiotic bacteria to suppress gut colonization of Y . ruckeri . Our study aimed to isolate and identify anti- Yersinia activity among lactic acid bacteria (LAB) isolated from the gastrointestinal tract (GIT) of aquatic animals. Of the 186 aquatic GIT isolates examined, three strains showed diffusible antimicrobial activity towards Y . ruckeri O1b. Analysis of 16 s rRNA gene sequences indicated the three bacterial strains were Enterococci , related to Enterococcus sp. (99%), Enterococcus thailandicus (99%), and Enterococcus durans (99%). Anti- Yersinia activity was maintained at neutral pH (~6.5–7.0), and in-vitro environmental tolerance assays showed the three strains could withstand simulated salmonids gastrointestinal tract conditions of: low pH (3.4) and 3% bile salt content. All three Enterococci strains showed higher adhesion to the intestinal mucus of Atlantic salmon than Y . ruckeri O1b ( E . durans 24%, E . enterococcus sp. 25% and E . thailandicus 98%, compared to Y . ruckeri O1b 5%). However, only Enterococcus sp. and E . thailandicus were able to grow in the salmon intestinal mucus broth while E . durans showed no growth. Anti- Yersinia activity was completely inactivated by proteinase-K treatment, suggesting that the active compound/s are proteinaceous and may be bacteriocin-like inhibitory substances (BLIS). Our data indicate that Enterococcus sp. MA176 and E . thailandicus MA122 are potential probionts for the prevention of yersiniosis in salmonids. Further in-vivo studies are required to determine whether these bacteria reduce the incidence of yersiniosis in Atlantic salmon.